Komunitas Apostolik Sebagai Paradigma Ekklesiologis: Kajian Kisah Para Rasul Dan Implikasinya Bagi Pelayanan Pastoral Gereja Kontemporer - Mudiantho Musa (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2026)
Many contemporary churches experience a significant gap between quantitative growth and the depth of ecclesiological quality, owing largely to pastoral ministry models that have become predominantly administrative-institutional in character and increasingly detached from their biblical roots. This study aims to examine the life patterns of the apostolic community as depicted in the book of Acts and to formulate an ecclesiological-pastoral framework applicable to the contemporary church. The approach employed is biblical hermeneutics through narrative-theological analysis of key texts in Acts 2:42–47, 4:32–35, and 6:1–7, supplemented by a systematic review of theological literature in systematic theology and practical ecclesiology. The analysis identifies four integrative dimensions of the apostolic community: (1) perseverance in apostolic didachē as the doctrinal foundation of communal life; (2) koinōnia that transcends formal fellowship toward genuine socio-economic solidarity; (3) communal worship centered on the breaking of bread and prayer as the formative ground of shared spirituality; and (4) organic martyria as the natural outgrowth of the community's integrity of life. Together, these four dimensions constitute a missional ecclesiology that inseparably unifies internal spiritual growth with external communal impact. This study contributes to the discourse of practical ecclesiology by proposing the apostolic community model not merely as a historical reference, but as an operational theological paradigm for the reconstruction of contextual pastoral ministry in contemporary Indonesian churches.